KARAKTERISTIK NUGET IKAN KEMBUNG (Rastrelliger kanagurta L) BEBAS GLUTEN DENGAN PENAMBAHAN TEPUNG PATI UMBI GANYONG (Canna edulis Kerr.) - Mulia, Air Ristya Wahyu; Pujiastuti, Veronica Ima; Purnawijayanti, Hiasinta Anatasia (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Children with autism spectrum disorder (ASD) are allergic to gluten products. Fish nuggets generally should not be consumed by children with autism because due to gluten (wheat flour) ingredients. This research developed gluten-free mackerel nuggets using ganyong flour as a filler. The study was to determine the effect of using ganyong flour on protein content, levels of omega-3 fatty acids, cooking loss, water holding capacity, sensory characteristics, and preference level for gluten-free mackerel fish nuggets. An experimental study with a completely randomized design (CRD) with three replications and four treatments. The addition of ganyong flour in mackerel nuggets was 0% (G0); 5% (G1); 10% (G2); 15% (G3); and 20%(G4). The best treatment was determined based on the result of the highest level of sensory preference. Mackerel nuggets with the addition of 10% canna flour as the best result, with characteristics are cooking loss (12%), water holding capacity (64.92%), protein content (14.05%), and omega-3 content (0.54%). The increase of ganyong flour (Canna edulis Kerr) affected the cooking loss, and sensory characteristics (p value <0,05). Mackerel fish nuggets and ganyong flour formulations can be categorized as gluten-free nuggets that can be consumed by children with ASD.